A Study on Feasibility of Wind Energy Production in Silivri Region by Using Laboratory Setup - Ozcira, Selin; Bekiroglu, Nur; Agcal, Ali (IEEE, 2013)
In this study, suitability of several factors have been investigated for site selection and the wind energy potential of that site is analyzed in laboratory conditions. A 7.5kW wind turbine with a 1.65m wing radius that is coupled to an induction machine is modeled with a 7.5kW motor-generator couple in the laboratory and their rotational speeds are adjusted through their drives to desired levels. A power analyzer is employed to perform the measurements and the collected data is evaluated. The laboratory experiments allowed monitoring the output current, voltage, and the power of the generator under varying drive speeds that emulates the changes in the wind speeds. Based on the increased load references applied to the generator, it is observed that the current from the generator increases; however, it is observed that the generator output voltage does not vary as the same rate. The contribution of this study is mainly using wind speed data in order to calculate rotor speed data by taking into account the lab setup as basic simulation test bench.
Keywords: wind energy; wind speed histogram; calculation of turbin rotor speed; SPEED; POWER; Energy & Fuels